Here's the question you clicked on:
mason4420
5(4x+5)+4(6x+5)+2=44x+48
20x+25+24x+20= 44x+48 44x+45= 44x+48 45 not equal to 48 as you can see this equality doesn't hold ...so no value of x (ans.) or either you hav posted wrong question.
also i just can't get this: \[\frac{ 1 }{ 5 }x+ \frac{ 1 }{ 3 }=1(\frac{ 2 }{ 3 }x+2)\]
regarding the answer above ! thank you sir! answer no value :'D
|dw:1359437471389:dw|
alwaz welcum................
thanks mann your awesome bro!! :) props
plss click the best reponse if u think i hav given u d best 1
5(4x+5)+4(6x+5)+2=44x+48 Multiply 5 by each term inside the parentheses. 20x+25+4(6x+5)+2=44x+48 Multiply 4 by each term inside the parentheses. 20x+25+24x+20+2=44x+48 Since 20x and 24x are like terms, add 24x to 20x to get 44x. 44x+25+20+2=44x+48 Add 20 to 25 to get 45. 44x+45+2=44x+48 Add 2 to 45 to get 47. 44x+47=44x+48 Since 44x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 44x from both sides. 44x+47-44x=48 Since 44x and -44x are like terms, add -44x to 44x to get 0. 0+47=48 Remove the 0 from the polynomial; adding or subtracting 0 does not change the value of the expression. 47=48 Since 47$48, there are no solutions. No Solution
(1)/(5)*x+(1)/(3)=1((2)/(3)*x+2) Multiply (1)/(5) by x to get (x)/(5). (x)/(5)+(1)/(3)=1((2)/(3)*x+2) Multiply (2)/(3) by x to get (2x)/(3). (x)/(5)+(1)/(3)=1((2x)/(3)+2) Remove the parentheses around the expression (2x)/(3)+2. (x)/(5)+(1)/(3)=(2x)/(3)+2 Since (1)/(3) does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting (1)/(3) from both sides. (x)/(5)=-(1)/(3)+(2x)/(3)+2 Simplify the right-hand side of the equation. (x)/(5)=(2x+5)/(3) Since there is one rational expression on each side of the equation, this can be solved as a ratio. For example, (A)/(B)=(C)/(D) is equivalent to A*D=B*C. x*3=(2x+5)*5 Multiply x by 3 to get 3x. 3x=(2x+5)*5 Multiply 5 by each term inside the parentheses. 3x=10x+25 Since 10x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 10x from both sides. 3x-10x=25 Since 3x and -10x are like terms, add -10x to 3x to get -7x. -7x=25 Divide each term in the equation by -7. -(7x)/(-7)=(25)/(-7) Simplify the left-hand side of the equation by canceling the common factors. x=(25)/(-7) Simplify the right-hand side of the equation by simplifying each term. x=-(25)/(7)